Local metal segregation as root cause for electrical shorts in highly doped pressure sensor devices. (November 2021) - Simon-Najasek, M.; Diehle, P.; Große, Ch.; Hübner, S.; Brokmann, G.; Sprenger, B.; Altmann, F.
Abstract: The fabrication of pressure sensor dies for precise and stable industrial applications requires a critical high dose implantation process strongly affecting the manufacturing yield of these devices. This paper describes a specific critical process related failure mechanism caused by this implantation process generating local electrical shorts within the piezo resistive structures in-built in the doped silicon substrate surface. The defect signature was investigated by applying site specific localization, advanced target preparation strategy and high-resolution electron microscopy to understand its process related root cause. The electrical shorts could be localized by Lock-in Thermography (LIT) and then were prepared by advanced laser and focused ion beam (FIB) based preparation in both cross-section and plan-view direction for in-depth investigation of the crystal defect signature by high resolution transmission electron microscopy (TEM) analysis in combination with energy dispersive X-ray spectroscopy (EDXS). As a result, the defect mechanism could be identified as segregation of embedded metal residues caused by Fe and Ni contamination from the high dose implantation equipment. Highlights: Implantation related defects can lead to reduced manufacturing yield of pressure sensor devices. Metal segregation in silicon devices can cause core-shell like crystal defects shorting pn-junctions. Combination of dedicated failure analysis methods can help to understand complex failure modes. Structural correlation is important to localize and investigate small scale defects in microelectronic devices.